What is Japanese cinema? : a history - Yomota, Inuhiko, 1953-; Kaffen, Phil (New York : Columbia University Press, 2019)
'What might Godzilla and Kurosawa have in common? What, if anything, links Ozu's sparse portraits of domestic life and the colorful worlds of anime? In this book, Yomota Inuhiko provides a concise history of Japanese film that shows how cinema tells the story of Japan's modern age. Discussing popular works alongside auteurist masterpieces, Inuhiko considers films in light of both Japanese cultural particularities and cinema as a worldwide art form. He covers the history of Japanese film from the silent era to the rise of J-Horror in historical, technological, and global contexts. Inuhiko shows how Japanese film has been shaped by traditional art forms such as kabuki theater as well as foreign influences spanning Hollywood and Italian neorealism. Along the way, he considers the first golden age of Japanese film; colonial filmmaking in Korea, Manchuria, and Taiwan; the impact of World War II and the U.S. occupation; the Japanese film industry's rise to international prominence during the 1950s and 1960s; and the challenges and technological shifts of recent decades. Alongside a larger thematic discussion of what defines and characterizes Japanese film, Inuhiko provides insightful readings of canonical directors including Kurosawa, Ozu, Suzuki, and Miyazaki as well as genre movies, documentaries, indie film, and pornography'--
Motion pictures: 1896-1918 -- The rise of silent film: 1917-1930 -- The first golden age: 1927-1940 -- Japanese cinema during wartime -- Film production in the colonies and occupied lands -- Japanese cinema under American occupation: 1945-1952 -- Toward a second golden age: 1952-1960 -- Upheaval amidst steady decline: 1961-1970 -- Decline and torpor: 1971-1980 -- The collapse of the studio system: 1981-1990 -- The indies start to flourish: 1991-2000 -- Within a production bubble: 2001-2011.
'Originally published in the Japanese as Nihon eigash 110 nen (Tokyo: Shueisha, 2014).'
Translated from the Japanese.
Includes bibliographical references : pages 201-213) and index.
Keywords: Motion pictures -- Japan -- History